2016
DOI: 10.2306/scienceasia1513-1874.2016.42.190
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity of Crocodylus porosus transthyretin protease and role of the terminal polypeptide sequences

Abstract: Human transthyretin (TTR), a recently identified protease, participates in the biology of high density lipoprotein and in the nervous system. In the present study, we determined whether TTR from a non-mammal Crocodylus porosus (crocTTR) has proteolytic activity and whether the N-and C-termini of the TTR polypeptide affect the proteolytic activity. The proteolytic activity of crocTTR and three chimeric crocTTRs: xenoN/crocTTR (crocTTR in which the N-terminal sequence was replaced with that of Xenopus laevis TTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…Moreover, a minor band of dimeric TTR with the mass ∼2 folds of monomeric TTR was observed in both mutated TTRs, which also similar to their wild types. This result was in accordance with other TTRs previously reported [9,19]. The dimer of TTR could be seen when TTR was not completely denatured even by heating under reducing condition for 30 min.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, a minor band of dimeric TTR with the mass ∼2 folds of monomeric TTR was observed in both mutated TTRs, which also similar to their wild types. This result was in accordance with other TTRs previously reported [9,19]. The dimer of TTR could be seen when TTR was not completely denatured even by heating under reducing condition for 30 min.…”
Section: Discussionsupporting
confidence: 93%
“…Our recent experiments showed that TTRs from Crocodylus porosus and Gallus gallus also have the proteolytic activity toward Aβ and other TTR substrates although the HXHXE motif does not exist [9,17]. Moreover, changing N-and/or C-terminal region of TTR, to be longer and more hydrophobic, increases its proteolytic activity [9]. From these findings, it raised the hypothesis that the sequence nearby the catalytic site, especially those in the Nand C-terminus of TTR, participate in the proteolytic mechanism of TTRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies demonstrated a connection between the alteration in length and hydropathy of the amino acid sequence of the N‐terminal segment of TTR and the binding affinities for thyroid hormone and RBP . A few changes of amino acid sequence have also been observed in the C‐terminal sequence of TTR and these were demonstrated to lead to an increase in the binding affinity for RBP and catalytic activity towards apolipoprotein A‐I . However, the effect of the changes in the C‐terminal region on the catalytic activity of TTR towards amidated NPY remains unknown.…”
mentioning
confidence: 99%